2020
DOI: 10.1002/jsfa.10725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the pre‐fermentative addition of chitosan on the nitrogenous fraction and the secondary fermentation products of SO2free red wines

Abstract: BACKGROUNDDifferent red winemaking were carried out to evaluate the effects of the prefermentative addition of chitosan, as an alternative to the use of SO2, on the secondary products of alcoholic fermentation, yeast available nitrogen (YAN), biogenic amines and ethyl carbamate.RESULTSThe wines made with chitosan presented higher total acidity and higher content of tartaric and succinic acids than those made only with SO2. The use of chitosan in winemaking resulted in wines with higher glycerol and diacetyl co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
2
4
0
1
Order By: Relevance
“…It is of note that all the treated wines presented a YAN concentration higher than that required to prevent standstills in fermentations. 45 Our results were in consonance with those observed by Marchante et al, 31 who evaluated the use of chitosan as an alternative to SO 2 in winemaking. The authors observed that the presence SD, standard deviation (n = 3).…”
Section: Amino Acids Ammonium Ion and Biogenic Amines In Verdejo Winessupporting
confidence: 92%
See 4 more Smart Citations
“…It is of note that all the treated wines presented a YAN concentration higher than that required to prevent standstills in fermentations. 45 Our results were in consonance with those observed by Marchante et al, 31 who evaluated the use of chitosan as an alternative to SO 2 in winemaking. The authors observed that the presence SD, standard deviation (n = 3).…”
Section: Amino Acids Ammonium Ion and Biogenic Amines In Verdejo Winessupporting
confidence: 92%
“…However, the pre‐fermentative addition of the different compounds or extracts modified the concentration of some wine components. Differences were found in dry extract and glycerol, which may be related to glycerol's capacity to readjust the osmotic gradient across the cell membrane so that cellular functions remained under osmotic stress conditions such as after the pre‐fermentative addition of solutes (i.e., GSH and ST99), as described for chitosan‐treated red wines 31 …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations